THE ETHICS OF AI IN HEALTHCARE: PRIVACY AND DATA SECURITY - Agarwal, Kshitiz; Gupta, Jaya; Shrivastava, Deepesh; Dadhich, Bhupendra (International Journal of Psychosocial Rehabilitation, 2020)
AI has done a major role in human life now. I have become a part of human life. I have done so many roles in various fields to make human life easy. Now AI is playing a role in healthcare. We see that lots of news about cybercrime and hacking of data and online fraud from accounts and other things hackers hack our mobile and keep text data, so some of our medicine data and our health data will be safe by machine learning and AI. We use things like phoneme and other things on the internet, and then we first give priority to our privacy. Then it is a general question of if AI will take a look at our health. It is an important thing, but if it is done, then how will our privacy be safe? How will our data and our cyber be saved from hackers? We know that hackers use lots of things to hack our data. If they hack our medicine and other medical reports, then it will be dangerous, so it is a general question for humans: if AI is used in their health sector, then how will they save your data?